Electric Drive. Dynamics. Laboratory guide: study aid - Obraztsov K. V. Konstantin Valentinovich (Томск, Изд-во ТПУ, 2019)
The laboratory guide contains description and guidelines of four laboratory worka carried out in courses "Basics of an electric drive", "Electric drive", "Automated electric drive" and is intended for students of all forms of education of Power and Electrics; Engineering Program. In the guide the registration procedure for studying dynamic modes of AC and DC electric drives and static characteristics of closed systems by analytical and experimental methods using computer technology has been listed. The study aid is intended for students of direction 13.03.02 "Power and Electrical Engineering".